Building The House of The Nation’s Civilization with Peace as The Foundation - Mutaqi, Ahmad Saifudin (Indonesian Journal of Interdisciplinary Islamic Studies (IJIIS), 2021)
Resistance to Indonesia's diversity can still be seen in the various incidents of intolerance and discrimination that occurred with political and religious backgrounds. There have been a number of issued government regulations that led to various interpretations and resulted in unjust public services, especially for some minority groups. It is not necessary for the government to impose restrictions on a person's basic religious practices or beliefs and regulate what kind of clothing a woman should wear, nor do they need to regulate what the physical form of a place of worship should be. Likewise, fellow citizens who interpret these regulations by themselves have the potential to decrease the public order. Hence the role of the state officials in enforcing the law is very important to achieve a peaceful society. Culturally, the reconciliation mechanisms in society can be developed when there is a desire to carry out a healthy dialogue. People are used to talking about different basic matters and they are respecting these differences so that they can work together for the benefit of the society. Dialogue is a communication process that considers semantic and pragmatic principles, where conversations with mutual understanding, acceptance, peaceful life and cooperation for mutual prosperity will arise. The atmosphere of a peaceful life is an important foundation for constructing a "house" of the nation's civilization. An important question that needs to be answered in this research is "what is the attitude of Islam in building peace to achieve the nation’s civilization?" This study seeks to explore the practical experiences of community life carried out by religious minority groups in responding to generally unfavorable situations. The research sources involved personal experiences and the spiritual leader’s statements that is implemented by the community members. It is hoped that the conclusion of this study will provide a positive and inspirational picture for the joint efforts of building the civilization of the society.